Reversal of Immunity After Clearance of Chronic HCV Infection—All Reset? - Wedemeyer, Heiner; Khera, Tanvi; Strunz, Benedikt; Björkström, Niklas K. (Frontiers in Immunology, 2020)
Chronic viral infections cause deterioration of our immune system. However, since persistent infections rarely can be eliminated, the reinvigoration capacity of an exhausted immune system have remained largely elusive. Chronic hepatitis C virus (HCV) infection can since some years be effectively cured with novel direct acting antiviral agents. Thus, it is now possible to study reversal of immunity in patients that are cured from a long-lasting chronic infection. We here highlight recent developments in the analysis of various immune cell populations during and after clearance of HCV infection. Surprisingly, whereas reinvigoration of certain immune traits clearly can be seen, many features of immune exhaustion persist over time after viral elimination. Thus, a long-term chronic insult to our immune system might result in irreversible damage to our immune system. This will be important to consider in therapeutic vaccination efforts against chronic infection and in development of immunotherapy based strategies against cancer.